Shear strength (shear vane) from IODP Hole 386-M0081A - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Shear strength from automated shear vane (AVS) of the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). This dataset was obtained at the end of the core processing workflow during the third phase (Personal Sampling Party, PSP) of expedition 386, which took place between 2022-11-15 – 2022-11-30 onboard D/V Chikyu. Measurements were performed on the work halves of core sections using a Wykeham-Farrance AVS. The apparatus consists of four vanes perpendicular to each other that are inserted in the sediment to their full length while attempting to minimize disturbance to the sediment. A motor loads a helical torsion spring and the bottom of the spring is united to the vane. Therefore, the bottom deflection of the spring records the angular displacement of the sediment, from which undrained shear strength has been calculated. Measurements were attempted approx. every 2 m throughout the core, though, some lithologies, especially in the upper few meters were too soft to obtain reasonable results. These core depths are blank in the Shear strength [kPa] column of the presented dataset. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023